Does overweight influence the prognosis of renal cell carcinoma? Results of a multicenter study. (26th November 2012) - Steffens, Sandra; Ringe, Kristina I; Schroeer, Katharina; Lehmann, Rieke; Rustemeier, Julia; Wegener, Gerd; Schrader, Mark; Hofmann, Rainer; Kuczyk, Markus A; Schrader, Andres J; ,
Abstract : Objectives: To assess the impact of overweight on prognosis of renal cell carcinoma patients. Patients And Methods: A total of 2030 patients who underwent surgery for renal cell carcinoma from 1990 to 2011 in three University Medical Centers were included in this retrospective analysis. For all patients, height and weight measurements at the time of diagnosis were available for review. The median (mean) follow up was 56.6 months (66.0 months). Results: A low body mass index was significantly associated with poor tumor differentiation, histology, microscopic vascular invasion and metastatic disease at the time of diagnosis. A lower‐than‐average body surface area – stratified according to the European average for men (1.98 m 2 ) and women (1.74 m 2 ) – was significantly related to older age, poor tumor differentiation, the histological subtype and microscopic vascular invasion. In addition, a low visceral fat area calculated in a subgroup of 133 evaluable patients was associated with a higher risk of advanced disease (pT3‐4 and/or N/M+) at diagnosis. The tumor‐specific 5‐year survival rate was 71.3, 78.7 and 80.1%, for patients with a body mass index of, <25, 25–30 and ≥30. Multivariate analysis confirmed body mass index as an independent prognostic factor. Conclusion: Our findings suggest that overweight represents an independent prognostic factor in renal cell carcinoma patients. Further research should address the question of why obese people have a higher incidence of renal cell carcinoma, but at the same time a significantly better prognosis than other patients, particularly in the case of localized disease.